Clinical Epidemiological Characteristics and Risk Factors for Severe Bronchiolitis Caused by Respiratory Syncytial Virus in Vietnamese Children - Sang Ngoc Nguyen; Thuy Ngoc Thi Nguyen; Lam Tung Vu; Thap Duc Nguyen (Hindawi Limited, 2021)
Introduction. Bronchiolitis is the most prevalent cause of hospitalization in infants under the age of 12 months. The disease is caused by respiratory syncytial virus (RSV) infection, which can cause breathing difficulties and respiratory failure. Therefore, it is necessary to discover the risk factors of severe bronchiolitis to diagnose and treat promptly. This study is aimed at describing the epidemiological characteristics and clinical features of acute bronchiolitis caused by RSV and assessing the related factors to severe acute bronchiolitis in studied patients. Methods. A descriptive cross-sectional study was carried out in Haiphong Children's Hospital, Haiphong, Vietnam, for one year, from October 1, 2016, to September 30, 2017. All bronchiolitis admissions<2 years were included. Results. 377 children were evaluated, including 261 boys and 116 girls; children under 6 months accounted for the highest proportion (57%), and 47 (12.5%) of all patients had severe disease. Wheezing was the main reason to be taken to the hospital 261 (69.2%). Clinical symptoms of acute bronchiolitis such as cough, tachypnea, and runny nose were found in all patients. Bronchiolitis cases increased in the winter-spring season, and the highest registered number of patients was 42 in March. Image of bronchiolitis on chest X-ray was found in all patients, and air trapping lung was found in 124 (32.9%) patients. The risk factors included age (≤6 months), low birth weight, preterm birth, nonbreastfeeding for the first six months, early weaning, and exposition to cigarette smoke increased the severe disease (p<0.05). Conclusion. The number of hospitalized infants with bronchiolitis caused by RSV has an upward trend during the winter-spring season (from October to March). This study confirms that age, preterm birth, breastfeeding under 6 months, history of exposure to cigarette smoking, low birth weight, having sibling(s) under five years old going to kindergarten, history of undergoing cesarean section, history of mechanical ventilation, poor living condition, and maternal education are 10 risk factors of severe bronchiolitis caused by RSV.